Tuberculosis Transmission Risk and IPC Practice Implementation by Students During Preventive Dentistry Procedures in the Dental Health Care Laboratory at Polkesmar - Sukini, Sukini; Ratuela, Jeineke; Sugiarta, Angga; Ulfah, Siti Fitria; Gita Wahyuningytyas, Miranda (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Tuberculosis (TB) remains a major concern in clinical health education settings due to its airborne transmission risk. This study aimed to analyze the risk of TB transmission and evaluate the implementation of Infection Prevention and Control (IPC) by students during preventive dentistry procedures in the JKG Care Service Laboratory at Poltekkes Semarang. Using a descriptive-analytic method with a cross-sectional survey design, data were collected from 60 students through structured questionnaires and direct observation. The results showed that 73% of students demonstrated moderate IPC behavior, and 67% of the laboratory conditions were rated as moderately compliant with standards. Bivariate analysis revealed no significant relationship between student IPC behavior and laboratory conditions (p = 0.885), but there was a significant relationship between IPC behavior and the implementation of preventive dentistry procedures (p = 0.012). These findings indicate that student compliance with IPC is more influenced by procedural application than environmental factors. Strengthening IPC training and supervision during clinical practice is crucial to minimize TB transmission risk in dental health education settings. Keyword: Infection, Tuberculosis, JKG Care Service Lab